Balanço hídrico climatológico com dados estimados pelo satélite tropical Rainfall Measuring Mission para a bacia hidrográfica do Rio Doce - Louzada, Franciane Lousada Rubini de Oliveira (2016)
Rainfall is important to calculate water availability of a region and its quality may affect the results of the water balance. Therefore data source with better spatial coverage is needed. The Tropical Rainfall Measuring Mission satellite -TRMM 3B43-v7 pr